2013
DOI: 10.3184/174751913x13812404042931
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of 5-Substituted 1H-Tetrazoles in Molten Tetrabutylammonium Bromide

Abstract: An economical and environmentally benign method for the synthesis of 5-substituted 1H-tetrazoles has been established. In this protocol, molten tetrabutylammonium bromide (TBAB) is used as both the solvent and catalyst. A mechanism involving the intermediacy of tetrabutylammonium azide (TBAN 3 ) is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…When acetate-based catalysts, such as Zn(OAc) 2 , Cu(OAc) 2 , and NH 4 OAc, were employed, the yield obtained was unsatisfactory compared to that obtained with the ZnCl 2 catalyst (Table 1, entries [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…When acetate-based catalysts, such as Zn(OAc) 2 , Cu(OAc) 2 , and NH 4 OAc, were employed, the yield obtained was unsatisfactory compared to that obtained with the ZnCl 2 catalyst (Table 1, entries [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…In an e ort to develop better reaction conditions, di erent solvents, such as DMSO, H 2 O, CH 3 CN, CHCl 3 , 1,4-dioxan, and toluene ( Table 1, entries [11][12][13][14][15][16], were screened for cycloaddition reaction in the presence of MCM-41SO 3 H as an e ective catalyst. The result indicated that the desired product was obtained in low yield as compared with DMF.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to aromatic nitriles, a wide range of alkyl nitriles, such as 4-chloro benzyl cyanide, benzyl cyanide, and malononitrile, react with NaN 3 under the optimized reaction conditions with subsided yield (Table 2 entries [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al [ 86 ] reported a simple and efficient protocol for the synthesis of a series of 5-substituted 1 H -tetrazoles ( 26 ) with excellent yields from the reactions of aryl nitrile ( 24 ) and sodium azide ( 25 ) in molten tetrabutylammonium bromide at 105 °C ( Scheme 12 ). In this reaction, molten TBAB played a dual role, both as a solvent as well as a catalyst.…”
Section: Applications Of Tbab For the Synthesis Of Bioactive mentioning
confidence: 99%